Análisis de la comunicación corporativa y su utilidad en la UTB - Varela Coloma, Diana Thalia (2020)
This research focused on the focus on the analysis of corporate communication and its usefulness at the Technical University of Babahoyo, as a strategic element to generate a holistic relationship and a corporate culture within the institution. The origin and evolution of the object of the research were analyzed through a diagnosis established within the University, considered to be relevant theoretical approaches and positions on the subject of research by renowned authors and experts in the field. Thanks to the survey and interview both for the rector and for employees and workers, the problem was deepened and in this way his views on the communication environment regarding the new infrastructure and the signage he has with the In order to keep people arriving for any reason informed to the institution. For this, a qualitative-quantitative approach was implemented, with qualitative predominance, and a type of descriptive research, characterized as a field survey; while the research line focused on the impact of communication on cultural development. The investigation determined that there is a strong internal relationship and corporate culture in the institution, which strengthens the identity and institutional image that has been very helpful in keeping those who visit the institution informed; For this reason, a solution proposal has been proposed, which consists of designing a strategic internal communication plan for the Babahoyo Technical University, in which the ideal strategies for improving institutional communication are identified. Its scope, viability and the objectives that would be achieved with it are explained.